2005
DOI: 10.1097/01.rli.0000163675.38490.6e
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Magnetic Resonance Imaging-Guided Localization of 131 Breast Lesions With Modified Embolization Coils

Abstract: Exact MRI-guided preoperative localization of exclusively MRI-detected breast lesions by using a modified embolization coil is feasible with excellent precision. Advantages over wire localization procedures are the possibility of specimen x-ray and the independence from time and place of operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…A recently developed score for classification of breast lesions seen on breast MRI can be translated into BIRADS categories and allows objective lesion assessment (2, 3). Though BIRADS categories are significantly correlated with histology, prediction of malignancy remains variable (4).…”
mentioning
confidence: 99%
“…A recently developed score for classification of breast lesions seen on breast MRI can be translated into BIRADS categories and allows objective lesion assessment (2, 3). Though BIRADS categories are significantly correlated with histology, prediction of malignancy remains variable (4).…”
mentioning
confidence: 99%
“…Previous studies of MRI-localized biopsies have reported an incidence of cancer ranging from 15% to 61% [7,[21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…30 Recently, automated devices for MR-guided breast biopsies and preoperative localization have been developed and might simplify the interventional workflow in the near future. 31,32 …”
Section: Impact On Cad Systems and Mr Guided Biopsymentioning
confidence: 99%